Recensão : "Corredor e rota : uma ordem mundial chinesa" de Bruno Maçães - Tavares, João António de Mendonça Vieira Lopes, 1991- (2024)
Lusíada. Política Internacional e Segurança. - ISSN 1647-1342. - S. 1, n. 29 (2024).